2001
DOI: 10.1002/ijc.1359
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in human colon carcinoma cells HT29 by sublethal cryo-injury: Mediation by cytochrome c release

Abstract: Cryosurgery is an emerging treatment for human solid tumors, notably colorectal liver metastasis. Cryosurgical procedures generate a thermal gradient of from at least -50 degrees C at the center of the tumor being treated to about 0 degrees C at the periphery. Cell death occurs by necrosis in the center, while the peripheral zone of frozen tumor harbors a mix of viable and dead tissue. In order to understand the mechanisms of cell death and survival in this peripheral area at risk for tumor recurrence, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 30 publications
(32 reference statements)
2
44
0
2
Order By: Relevance
“…19,35 Before these reports, freeze rupture and necrosis were the only forms of cell death thought to be associated with cryoablation. 12 The advent of apoptosis activation provided a novel opportunity to manipulate freezing-induced cell death in an attempt to improve procedural efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,35 Before these reports, freeze rupture and necrosis were the only forms of cell death thought to be associated with cryoablation. 12 The advent of apoptosis activation provided a novel opportunity to manipulate freezing-induced cell death in an attempt to improve procedural efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, other studies have reported on the activation of apoptosis following the application of freezing. [17][18][19] Because of the resistant nature of CaP cells to freezing, 18,20 physicians are required to extend the freeze zone significantly beyond the diseased tissue, exposing a greater portion of the non-targeted, healthy tissue to cryoablation. 10,12 Inadequate management of the freeze zone periphery (positive freeze margin) can sometimes have a negative effect on the surrounding tissues (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, i.v. injections of hMSCs that were made apoptotic by repeated cycles of freezing and thawing (16) did not have any effects on corneal graft survival and EAU development (Fig. S2).…”
Section: Msc Pretreatment Improves Cornealmentioning
confidence: 94%
“…It is established that cryosurgery, in addition to necrosis, could trigger apoptosis, and a few studies have implicated the mitochondrial pathway of apoptosis (Hanai et al, 2001;Baust et al, 2004). Clarke et al (2004) showed that freezing and chemotherapy differentially activated Bcl-2 family members in a human prostate cancer cell line.…”
Section: Discussionmentioning
confidence: 99%